Interacción genotipo-ambiente en ganado Holstein colombiano (2001)
ABSTRACT: The existence of Genotype-Environment Interactions among four regions of Colombia was investigated. The information was obtained from records of Holstein cattle in Cundinamarca (C), Valle del Cauca(V), Antioquia (A) and Nariño (N). A mixed models multivariate analysis methodology, applied to an animal model for repeated measures was used. Variance components were estimated by Derivative Free Restricted Maximum Likelihood algorithm (DFREML). Contemporary group (Herd-year) and genetic group of the sires (origin-year of birth) were fixed effects, and the genetic additive, permanent environment and temporary environment were included as random effects. Production records (n = 69464) of 25 608 daughters of 594 sires were used. Genetic correlation coefficients of milk production between regions were 0.70, 0.83, 0.73, 0.95, 0.97 and 0.99 for C-V, C-A, C-N, V-A, V-N and A-N, respectively. Different genetic, permanent environment and residual variances among areas were observed, but heritabilities and repetibilities were similar. Genotype and Environment Interaction exists, mainly between Cundinamarca and the other three regions.